Prevention of burn injuries in low- and middle-income countries: A systematic review. Issue 6 (September 2016) - Rybarczyk, Megan M.; Schafer, Jesse M.; Elm, Courtney M.; Sarvepalli, Shashank; Vaswani, Pavan A.; Balhara, Kamna S.; Carlson, Lucas C.; Jacquet, Gabrielle A.
Highlights: Education-based burns prevention initiatives in LMICs show favorable outcomes. Outcomes research is lacking: only eleven studies were identified in this systematic review. More research on initiatives targeted to groups at the highest risk for burns is needed. Abstract: According to the World Health Organization (WHO), burns result in more than 250, 000 deaths and the loss of approximately 18 million disability adjusted life years (DALYs), more than 90% of which occur in low- and middle-income countries (LMICs), annually. This type of serious injury – one that is particularly devastating in LMICs – is preventable. To further explore the effectiveness of burn prevention strategies in LMICs, we performed a systematic review of the literature indexed in PubMed, EMBASE, Web of Science, Global Health, and the Cochrane Library databases as of October 2015. Our search resulted in 12, 568 potential abstracts. Through multiple rounds of screening using criteria determined a priori, 11 manuscripts were identified for inclusion. The majority of these studies demonstrate reductions in hazardous behaviors, incidence of burns, morbidity, and mortality using educational programs, but also highlight other initiatives, such as media campaigns, as effective strategies. Given that only 11 manuscripts are highlighted in this review, it is evident that original research is lacking. Further studies of preventative efforts tailored to populations in LMICs are needed. It is also essential that these studies be founded in population-based epidemiology and use meaningful end points, such as reductions in incidence, morbidity, and mortality.